Urticarial rash of pregnancy turning into a rare and scary dermatosis of pregnancy: a case report and review of literature - Ahuja, Mayuri; Srivastava, Ruchi; Agarwal, Shelly; Agarwal, Niharika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Dermatosis of pregnancy encompasses a group of skin conditions that occurs due to interaction of multiple factors in the body during pregnancy or during post-partum period. We presented a case of 25-year-old G4P1L1A2 with initial symptom of urticarial rash which later progressed to a rare and a scary dermatosis of pregnancy which became a challenge both to the obstetrician and the dermatologist.